Identification and evaluation of new Mycobacterium bovis antigens in the in vitro interferon gamma release assay for bovine tuberculosis diagnosis - Eirin, Maria Emilia (2015)
Bovine tuberculosis (bTB) is a common zoonotic disease, caused by Mycobacterium bovis (M. bovis), responsible for significant economic losses worldwide. Its diagnosis is based on the detection of cell mediated immunity under the exposure to protein purified derivative tuberculin (PPD), a complex and poorly characterized reagent. The cross-reactivity to non-tuberculous mycobacterium species (false-positive results) has been crucial to develop a more proper antigen. In the present study, we selected six M. bovis Open Reading Frames (Mb1992, Mb2031c, Mb2319, Mb2843c, Mb2845c and Mb3212c) by in-silico analysis and evaluated them in experimental and natural infection; none of these antigens had been previously assessed as diagnostic antigens for bTB. The reactivity performance was tested in animals with both positive and negative Tuberculin Skin Test (TST) results as well as in cattle infected with Mycobacterium avium subesp. paratuberculosis (MAP). The six recombinant antigens individually induced an IFN-γ response, with overall responder frequency ranging from 18.3 to 31%. Mb2845c was the most valuable antigen with the potential to discriminate TST-positive cattle from either TST-negative or MAP infected animals. Mb2845c showed similar performance to that observed with ESAT-6 and PPD-B among TST and MTC specific-PCR positive animals, although this result needs to be proven in further studies with a higher sample size. Our data confirm the feacibility to implement bioinformatic screening tools and suggest Mb2845c as a potential diagnostic antigen to be tested in protein cocktails to evaluate their contribution to bTB diagnosis.